Nilai Perusahaan dan Analisis Investasi Pada Bank Daerah Bangka Belitung - Sumiyati, Sumiyati; Wardhani, Rulyanti Susi; Yokotani, Yokotani; Saputri, Angelia (Forum Kerjasama Pendidikan Tinggi, 2022)
Risk absorption and capital addition is a business strategy for business development in order to face intense competition in the banking industry. One of the Regional Development Banks in Indonesia is the Regional Development Bank of South Sumatra and Bangka Belitung. Before making investment decisions, investors need information about company value by reading and analyzing financial reports. The higher the value of the company, the more favorable perceptions investors will have of the company so that in the end they have the confidence to invest. Information about company value is also important for companies to assess their performance. In general, financial performance is analyzed using financial ratios. This study uses a mixed approach which is complemented by financial statement analysis. Methods of data analysis using ARIMA least squares regression analysis and investment analysis. The results showed that it was concluded that the company is in a progressive position (Strength Opportunity) with the SWOT method. The results of the ARIMA Least Square regression analysis concluded that the ratios of NPL, NIM, LDR, CASA, CR and BOPO are strongly related to firm value. However, the variables that have the most influence on firm value are DER, CASA and CAR. The results of the investment analysis show that the rate of return on investment (ROCE) is 14.54 more than the capital provided, Payback Period is 1 year 8 months. While the results of the Net Present Value (NPV) calculation are positive, which means the project can be continued and has good prospects in the future, while the Internal Rate of Return (IRR) shows a project interest rate of 34.36% or greater than the discount rate by 14.25%.